A scalable mediator approach to process large biomedical 3-D images. - Liakos, K. (IEEE Transactions on information technology in biomedicine)
The Edinburgh Mouse Atlas is a spatial-temporal framework to store and analyze biological data including three-dimensional (3-D) images that relate to mouse embryo development. The purpose of the system is the analysis and querying of complex spatial patterns, in particular the patterns of gene activity during embryo development. The framework holds large 3-D gray level images and is implemented in part as an object-oriented database. In this paper, we propose a dynamic layered architecture, based on the mediator approach, for the design of a transparent and scalable distributed system which can process objects that can exceed 1 GB in size. The system's data are distributed and/or declustered across a number of image servers and are processed by specialized mediators.